Energy Efficiency Influence on Building Value According to Present Cost Value Method - Rojas Kovach, Axa (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>The house`s value based on its energy efficiency, constitutes a valuation process that is sustained in the economic yield of a building; every time that has settled down an efficiently power building, it is characterized to offer to his usuary savings in his power consumptions without it affects the thermal comfort. The energy efficiency can be described and, this qualification constitutes a judgment element to establish elements of judgment been worth to differentiate the constructions through its quality. Particularly the houses, are the constructions but susceptible to be classified by means of the degree of energy efficiency that these can offer from the beginning to their users of the diminution of the consumption of final energy. This energic qualification can be obtained by means of the use of programs of computation designed to carry out the simulation of the thermal behavior of the constructions and since the obtained results this construction through the analysis of the cost in present value can be valued from the optics of the energy efficiency, which is sustained in the advance payment of the cash flow